Gagagsan Pengaturan Sanksi Tindak Pidana Pembunuhan Anggota Keluarga Dalam Pembaharuan Hukum Pidana Di Indonesia - Dahniel, Maida Aulia; Deliana, Evi; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Murder is a criminal act. There have been many criminal acts by criminal law experts. Nowadays killing is not only done to others, but murders in the family are common today. This matter caused by trivial factors or problems, usually economic problems. Murder of a family member is a murder is a murder whose victim is family who still have blood ties, or family ties to the perpetrator murder. It is not regulated regarding the setting of sanctions for murder that occurs in family. Murder is a type of criminal offense whose actions against justice. The offense of murder in the Japanese criminal Code exists teexception to the perpetrator who killed his own parents, a straight line up or the parents of the wife or husband are straight line up, are threatened with serious punishment, namely criminal death or life imprisonment for forced labor. The objectives to be achieved in this research are the first: that isto know what factors caused murder in the family. Second,to know the sanctions applied in the crime of murder against family members in Indonesian positive law and how it is applied. Third, in order to know the idea related to the regulation of the criminal act of murder against future family members in Indonesian. The author did research using normative juridical methods or literature studies in order to obtain secondary data which is divided into 3 (three), namely primary and secondary legal materials and tertiary. In this study, the researcher uses a statutory approach that will examine the law, namely the principle of justice which has a relationship to the problem under study. From the results of the study there are three main things that can be concluded: first about the factors that cause the perpetrator to commit murder. Second, legal arrangements regarding crimes against life are regulated in the Criminal Code (KUHP). Not regulated regarding the setting of sanctions murder that occurs in the family. The three ideas regarding the imposition of sanctions Criminal punishment for perpetrators of murder against family members is a minimum of 20 years imprisonment and plus a third if it is planned and if it is done spontaneously then a minimum sentence of 15 years in prison and a third of the sentenceis added. Authors suggestions, murder cases against family members in Indonesia increasing day by day. Therefore, the state must renew Laws regarding sanctions against murderers who commit murder towards his family members. As well as suggesting that the imposition of sanctions on the perpetrators of the murder of family members are given severe sanctions, namely: a minimum of 20 years in prison and an additional one third it is planned and if it is done unplanned or spontaneously, it is punishable by 15 years in prison plus a third. Keywords: Murder-Criminal-Idea-Family-Sanction Arrangemnt